Industrial and Organizational Psychology / Research and Practice - Spector Paul E (John Wiley And Sons, Inc, 2006)
Creating a more productive and healthier workforce is a balancing act. Introduction, Research Methods in I/O Psychology, Assessment of Jobs and Performance and People, Job Analysis, Performance Appraisal, Assessment Methods for Selection and Placement, Selecting Employees, Training, The Individual and the Organization, Theories of Employee Motivation, Feelings about Work, Productive and Counterproductive Employee Behavior, Occupational Health Psychology, The Social Context of Work, Work Groups and Work Teams, Leadership and Power in Organizations, Organizational Development and Theory, Appendix, References, Glossary, Name and Subject Index, Photo Credits.